2012
DOI: 10.1021/nl300524j
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Nanocrystal-Coated Glass Fibers for High-Performance Thermoelectric Energy Harvesting

Abstract: Recent efforts on the development of nanostructured thermoelectric materials from nanowires (Boukai, A. I.; et al. Nature 2008, 451, (7175), 168-171; Hochbaum, A. I.; et al. Nature 2008, 451, (7175), 163-167) and nanocrystals (Kim, W.; et al. Phys. Rev. Lett. 2006, 96, (4), 045901; Poudel, B.; et al. Science 2008, 320, (5876), 634-638; Scheele, M.; et al. Adv. Funct. Mater. 2009, 19, (21), 3476-3483; Wang, R. Y.; et al. Nano Lett. 2008, 8, (8), 2283-2288) show the comparable or superior performance to the bulk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 25 publications
1
75
0
Order By: Relevance
“…[5][6][7][8] Such devices can be utilized for building the self-powered systems, which can independently operate by harvesting the energies in the ambient environment without any external electrical powering systems. Among the various kinds of energies, the mechanical energies such as the air ow, vibration and object movement have wide distributions and low limitation by the environmental conditions, which can be harvested and converted into electricity by using piezoelectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Such devices can be utilized for building the self-powered systems, which can independently operate by harvesting the energies in the ambient environment without any external electrical powering systems. Among the various kinds of energies, the mechanical energies such as the air ow, vibration and object movement have wide distributions and low limitation by the environmental conditions, which can be harvested and converted into electricity by using piezoelectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…[ 100,101 ] The obvious benefi t of the thermoelectric NGs is the extensive distribution of thermal energy.…”
Section: Thermoelectric and Pyroelectric Ngsmentioning
confidence: 99%
“…Particularly, flexibility can allow thermoelectric devices to be installed on curved surfaces such as automobile exhaust pipes, power plant steam pipes, manufacturing industry cooling pipes, and so forth. Our previous studies 2 showed that thermoelectric fibers made from glass fibers coated with an ultrathin layer of PbTe nanocrystals (300 nm thick) can possess a similar thermoelectric figure of merit compared to traditional rigid bulk bismuth telluride modules. The module assemblies require several millimeters of thickness, which highlights a great potential for high performance with much reduced raw material cost for the coated fibers.…”
mentioning
confidence: 99%
“…21−23 The fabrication of the PbTe-coated thermoelectric glass fibers follows the procedure described in our previous studies. 2 First, we synthesize PbTe nanocrystals by hot injection of trioctylphosphine-tellurium (TOP-Te) into a lead oleate solution. The chemicals including 1-octadecene (ODE, 90%), oleic acid (OA, 90%), lead(II) oxide (PbO, 99.9+%), tellurium powder (99.8%), hexane (98.5%), acetone (99.5%), chloroform (99%), hydrazine hydrate solution (80%), and acetonitrile (99.8%) were purchased from Sigma-Aldrich and used without further purification.…”
mentioning
confidence: 99%